Dlaczego i jak uczyć o Holokauście na lekcjach języka polskiego w gimnazjum - Karkut, Dorota (Dydaktyka Polonistyczna, 2015)
The article presents ways of introducing topics concerning the extermination of Jews duringthe Second World War by the Polish language teachers during lessons at the junior secondary school.These proposals concern analysis and interpretation of literary texts in the context of the cultureand the modern art as well as the Internet. It discusses various methods which can be useful at thework of the teacher and the student. Among others these are drama and project. This article drawsattention to the need for integration of Polish language knowledge and history knowledge so thatthe Holocaust was not repeated.